Ketahanan padi (Oryza sativa L.) varietas IPB 3S terhadap wereng batang cokelat (Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Nurdaaniyah, Andi; Dadang, Dadang; Winasa, I Wayan (Jurnal Entomologi Indonesia, 2020)
Brown planthopper (Nilaparvata lugens (Stål)) is one of the major rice insect pests that is known to cause high loss of rice production. One of the strategies to control this pest is by using resistant rice varieties. The aim of this research was to study the resistance of IPB 3S variety to BPH by measuring BPH fecundity, sex ratio, feeding activity as well as population increase compared to Ciherang variety against brown planthopper (N. lugens). Fecundity test used a pair of BPH adult infested on 21 days after planting (DAP) of rice plants. Eggs laid in rice stalks and the rest of eggs in the ovary were counted. In order to know the change of sex ratio, a pair of BPH adults was infested on 30 DAP rice plants and allowed to lay eggs. The calculation of sex ratio was conducted at adult stage of BPH by segregation between male and female adults. Feeding activity of BPH was evaluated using ninhydrin and analyzed qualitatively using spectrophotometer. Ten fourth instar nymphs of BPH was infested on 30 DAP old of rice seedlings. Honeydew secreted by BPH was collected to filter paper sprayed with ninhydrin. Population increased test was conducted by infesting five pairs of BPH adults on 35 DAP old rice plants. Observations was conducted on nymph and adult stages. Each test was replicated 10 times. In general, IPB 3S is slightly resistant to BPH, compared to Ciherang variety. The feeding activity of BPH is higher in Ciherang compared to IPB3S. However, the fecundity and population increased of BPH in Ciherang is similar to IPB3S.